Incidence and species distribution of candidaemia in Asia: a laboratory-based surveillance study. (October 2015) - Tan, B.H.; Chakrabarti, A.; Li, R.Y.; Patel, A.K.; Watcharananan, S.P.; Liu, Z.; Chindamporn, A.; Tan, A.L.; Sun, P.-L.; Wu, U.-I.; Chen, Y.-C.; ,
Abstract: The epidemiology of candidaemia varies between hospitals and geographic regions. Although there are many studies from Asia, a large-scale cross-sectional study across Asia has not been performed. We conducted a 12-month, laboratory-based surveillance of candidaemia at 25 hospitals from China, Hong Kong, India, Singapore, Taiwan and Thailand. The incidence and species distribution of candidaemia were determined. There were 1601 episodes of candidaemia among 1.2 million discharges. The overall incidence was 1.22 episodes per 1000 discharges and varied among the hospitals (range 0.16–4.53 per 1000 discharges) and countries (range 0.25–2.93 per 1000 discharges). The number of Candida blood isolates and the total number of fungal isolates were highly correlated among the six countries ( R ² = 0.87) and 25 hospitals ( R ² = 0.77). There was a moderate correlation between incidence of candidaemia and the intensive care unit (ICU)/total bed ratio ( R ² = 0.47), although ICUs contributed to only 23% of candidaemia cases. Of 1910 blood isolates evaluated, Candida albican s was most frequently isolated (41.3%), followed by Candida tropicalis (25.4%), Candida glabrata (13.9%) and Candida parapsilosis (12.1%). The proportion of C. tropicalis among blood isolates was higher in haemato-oncology wards than others wards (33.7% versus 24.5%, p 0.0058) and was more likely to be isolated from tropical countries than other Asian countries (46.2% versus 18.9%, p 0.04). In conclusion, the ICU settings contribute, at least in part, to the incidence variation among hospitals. The species distribution is different from Western countries. Both geographic and healthcare factors contribute to the variation of species distribution.